IDENTIFYING THE RELATIONSHIP BETWEEN MENTAL HEALTH AND WORK PERFORMANCE: A CROSS-SECTIONAL STUDY IN BANTEN PROVINCE - Yuda Nabella Prameswari; Ichwan Delfecio; Siti Darifah (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2026)
Background: In the context of global competition, industrial companies must prioritize strategic factors, particularly the development and well-being of human resources. In Indonesia’s manufacturing sector, especially in Banten Province, employees are often subjected to considerable stress resulting from irregular working hours and demanding production targets. Mental health frequently overlooked by employers and organizational systems has a direct and significant impact on employee performance, influencing productivity, motivation, and work quality. Objective: To identify the relationship between mental health and work performance of manufacturing plant employees at PT. X in Banten Province. Methods: This study uses an analytical observational method with a cross-sectional design to examine 396 employees at PT. X's paper packaging plant in Serang City, selected through purposive sampling based on inclusion and exclusion criteria. Data were collected with a questionnaire using the DASS and IWPQ scales and analyzed using the Chi-square test. Results: This study found that depression, anxiety, and stress were each significantly associated with work performance (all p < 0,001), with stress having the strongest effect (OR = 4,062; 95% CI = 2,362–6,985). Conclusion: Depression, anxiety, and stress are significantly associated with reduced work performance among employees at PT. X. Therefore, employers and policymakers should prioritize implementing comprehensive mental health programs and supportive workplace policies to enhance employee well-being and improve productivity in the manufacturing sector.